Hubungan Komunikasi Terapeutik Perawat dengan Tingkat Kecemasan Pasien Pre Operasi di RSI Pekajangan - Umi Musarofah; Dwi Retnaningsih; Maulidta Karunianingtyas Wirawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Preoperative anxiety is one of the psychological problems that patients often experience and can affect physiological stability, response to anesthesia, and the postoperative recovery process. High levels of anxiety in patients leading up to surgery can have negative impacts, both physically and emotionally. One of the interventions that can be done to reduce anxiety is therapeutic communication by nurses. Therapeutic communication has an important role in creating a relationship of mutual trust, providing a sense of security, and helping patients understand the medical procedures to be undertaken. However, there are still conditions where therapeutic communication has not been implemented optimally. This study aims to determine the relationship between nurses' therapeutic communication and the level of anxiety of preoperative patients at RSI Pekajangan. The study used a quantitative approach with a correlational design and involved 72 respondents who were selected through purposive sampling techniques. The research instruments included a therapeutic communication questionnaire and the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Data analysis was carried out using the Spearman Rank test. The results showed that most respondents rated therapeutic communication in the categories of good (81.9%) and moderate anxiety (72.2%). Statistical tests showed a significant relationship between nurses' therapeutic communication and preoperative patients' anxiety levels (p = 0.027) and moderate correlation strength (r = -0.260). The conclusion of this study confirms that therapeutic communication plays a role in lowering patients' anxiety, so it is recommended that nurses improve therapeutic communication skills as part of pre-surgical interventions.